Electropolymerization of Octakis Diethlyamino Substituted Metallophthalocyanines and Their Electrochromic Characterization - KOCA, ATIF (ELECTROCHEMICAL SOC INC, 2015)
Metallophthalocyanines (MPcs) bearing octakis diethylamino-phenoxy substituents were oxidatively electropolymerized on the working electrode. Changing metal center of the Pc cores of MPcs (MPcs bearing octakis diethylamino-phenoxy (odea) groups; M = 2H(+) (H2Pc-odea); Co2+ (CoPc-odea) and Cu2+ (CuPc-odea) alter the electropolymerization mechanisms and electrochemical responses of the electropolymerized films. Redox activities and insolubility of the electropolymerized films of the complexes provided usage of the complexes in different electrolytic media as electroactive materials. For electrochromic applications, thin films of the complexes were coated on ITO electrodes and ITO/MPc-odea electrodes were constructed. Then electrochromic properties of ITO/MPc-odea electrodes were studied in detail with various electrochemical, in-situ spectroelectrochemical and in-situ electrocolorimetric analysis methods. While ITO/H2Pc-odea did not give any spectral changes in different electrolytes, both of ITO/CuPc-odea and ITO/CoPc-odea gave excellent electrochromic responses with distinct color changes, fast response times, high optical contrast and reasonable optical and coulombic stabilities. (C) 2015 The Electrochemical Society. All rights reserved.
Keywords: NEAR-INFRARED ELECTROCHROMISM; LANGMUIR-BLODGETT-FILMS; THIN-FILMS; SPECTROELECTROCHEMICAL PROPERTIES; METAL-FREE; PHTHALOCYANINES; DEVICES; BISPHTHALOCYANINES; COMPLEX